1990
DOI: 10.2307/2393392
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Organizational Cultures: A Qualitative and Quantitative Study Across Twenty Cases

Abstract: This paper presents the results of a study on organizational cultures in twenty units from ten different organizations in Denmark and the Netherlands. Data came from in-depth interviews of selected informants and a questionnaire survey of a stratified random sample of organizational members. Data on task, structure, and control characteristics of each unit were collected separately. Quantitative measures of the cultures of the twenty units, aggregated at the unit level, showed that a targe part of the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
1,583
1
245

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,373 publications
(1,943 citation statements)
references
References 28 publications
34
1,583
1
245
Order By: Relevance
“…Measures of variability of behavior are as readily available as measures of means and should also be reported in cross-cultural studies. The notion that organizational cultures differ on the extent to which they emphasize rules and predictability versus flexibility and experimentation has a long history in the organizational sciences (Litwin & Stringer, 1968;O'Reilly, Chatman, & Caldwell, 1991;O'Reilly & Chatman, 1996;Quinn, 1988;Rousseau, 1990 shown that flexibility and experimentation versus rule orientation is a central dimension of organizational culture (Dastmalchian, Lee, & Ng, 2000;Hofstede, Neuijen, Ohayv, & Sanders, 1990;Verberg, Drenth, Koopman, van Muijen, and Wang, 1999).…”
Section: Societal Tightness-looseness and Cross-level Effects On Indimentioning
confidence: 99%
“…Measures of variability of behavior are as readily available as measures of means and should also be reported in cross-cultural studies. The notion that organizational cultures differ on the extent to which they emphasize rules and predictability versus flexibility and experimentation has a long history in the organizational sciences (Litwin & Stringer, 1968;O'Reilly, Chatman, & Caldwell, 1991;O'Reilly & Chatman, 1996;Quinn, 1988;Rousseau, 1990 shown that flexibility and experimentation versus rule orientation is a central dimension of organizational culture (Dastmalchian, Lee, & Ng, 2000;Hofstede, Neuijen, Ohayv, & Sanders, 1990;Verberg, Drenth, Koopman, van Muijen, and Wang, 1999).…”
Section: Societal Tightness-looseness and Cross-level Effects On Indimentioning
confidence: 99%
“…Esses autores postulam que a cultura organizacional se revela por intermédio de práticas culturais, tais como rituais, símbolos e heróis, as quais refletem as dimensões e os valores mais inconscientes das organizações que ditam suas alternativas para lidar com o ambiente, não sendo, portanto, diretamente observáveis. Hofstede et al (1990) propõem a abordagem dos valores organizacionais como núcleo sustentador de práticas e de comportamentos que configuram as culturas de cada organização. Os autores defendem a mensuração da cultura com base na percepção que os membros têm acerca dos valores existentes e praticados em cada instituição.…”
Section: Discussionunclassified
“…Besides values, this construct also includes other layers of organizational members' mental schemes, such as assumptions, norms, attitudes, etc., but values are often underlined as the central element of organizational culture's content (Schein & Schein, 2017;Janicijevic, 2013;Hofstede, Neuijen, Ohayiv & Sanders, 1990). Unlike individual values, collective values as organizational culture element synchronously guide the behaviour of many organizational members, thus creating the effect of coordinated collective action, which is the foundation of the very organization.…”
Section: The Theoretical Frameworkmentioning
confidence: 99%